Oral, but not topical, sodium bicarbonate improves repeated sprint performance during simulated soccer match play exercise in collegiate athletes. - Gurton, W. H.; Gough, L. A.; Siegler, J. C.; Lynn, A.; Ranchordas, M. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
This study investigated the effect of oral and topical sodium bicarbonate (SB) on soccer-specific performance during simulated soccer exercise. In a block randomized, double-blind, crossover design, 10 collegiate male soccer players (stature: 181.7 ± 3.2 cm, body mass: 81.7 ± 10.5 kg) performed soccer-specific performance tests (countermovement jumps, Illinois agility, 8 × 25 m repeated sprints) throughout a 90-min soccer-specific aerobic field test (SAFT90) following 0.3 g/kg body mass SB in capsules (SB-ORAL), 0.9036 g/kg body mass PR Lotion (SB-LOTION), or placebo capsules and lotion (PLA). Soccer-specific performance tests were conducted pre-SAFT90, during half-time and post-SAFT90. Blood samples were analyzed for acid-base balance (pH; bicarbonate, HCO-3) and strong ions (sodium, Na+; potassium, K+). Average sprint times were quicker for SB-ORAL than PLA during half-time (3.7%; p = .049; g = .57) and post-SAFT90 (4.9%; p = .041; g = .66). SB-ORAL increased pH and HCO-3 prewarm-up and during half-time (p < .05), and lowered K+ during half-time (p = .035) compared with PLA. SB-LOTION increased pH (p = .019) and lowered K+ (p = .012) during half-time compared with PLA. SB-LOTION increased Na+ postexercise compared with PLA (p = .008). Repeated sprint times during simulated soccer exercise improved for SB-ORAL, which might have been mechanistically underpinned by elevated blood buffering capacity and greater regulation of strong ion concentration. Consuming SB in capsules is a more effective strategy than topical SB application for improving blood buffering capacity and repeated sprint performance throughout competitive soccer matches.